Weighted damping of external and initial disturbances in descriptor control systems - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.925.51; 681.5.03 We investigate the problem of H_∞ -control of a generalized type for a class of linear descriptor systems and suggest a criterion and sufficient conditions for the existence of control laws ensuring that the closed-loop system is regular, stable and impulse-free with a desired estimate for the weighted damping level of external and initial disturbances. The main computational procedures for the synthesis of regulators are reduced to solving linear and quadratic matrix inequalities that have no rank constraints. An example of robust stabilization of a hydraulic system with three tanks is given.